2017
DOI: 10.1371/journal.ppat.1006451
|View full text |Cite
|
Sign up to set email alerts
|

A human endogenous retrovirus-derived gene that can contribute to oncogenesis by activating the ERK pathway and inducing migration and invasion

Abstract: Endogenous retroviruses are cellular genes of retroviral origin captured by their host during the course of evolution and represent around 8% of the human genome. Although most are defective and transcriptionally silenced, some are still able to generate retroviral-like particles and proteins. Among these, the HERV-K(HML2) family is remarkable since its members have amplified relatively recently and many of them still have full length coding genes. Furthermore, they are induced in cancers, especially in melano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(106 citation statements)
references
References 68 publications
3
96
0
Order By: Relevance
“…53 An in vitro experiment showed that HERV-K env protein effectively activated the ERK1/2 pathway and induced epithelialmesenchymal transition in a nontumorigenic human breast epithelial cell line, suggesting that this HERV-K env protein has oncogenic properties. 54 Moreover, HERV-K expression was significantly associated with poor outcome in hepatocellular carcinoma patients, 55 as well as cancer progression in soft tissue sarcoma. 56 Elevated HERV-K gag expression in PBMC was associated with prostate cancer diagnosis particularly in older men and smokers who tend to develop a more aggressive disease.…”
Section: Other Herv Families In Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…53 An in vitro experiment showed that HERV-K env protein effectively activated the ERK1/2 pathway and induced epithelialmesenchymal transition in a nontumorigenic human breast epithelial cell line, suggesting that this HERV-K env protein has oncogenic properties. 54 Moreover, HERV-K expression was significantly associated with poor outcome in hepatocellular carcinoma patients, 55 as well as cancer progression in soft tissue sarcoma. 56 Elevated HERV-K gag expression in PBMC was associated with prostate cancer diagnosis particularly in older men and smokers who tend to develop a more aggressive disease.…”
Section: Other Herv Families In Cancersmentioning
confidence: 99%
“…Furthermore, HERV‐K antibodies and mRNA are elevated in blood of patients at an early stage of breast cancer and further increased in patients who are at risk of developing metastatis . An in vitro experiment showed that HERV‐K env protein effectively activated the ERK1/2 pathway and induced epithelial‐mesenchymal transition in a nontumorigenic human breast epithelial cell line, suggesting that this HERV‐K env protein has oncogenic properties . Moreover, HERV‐K expression was significantly associated with poor outcome in hepatocellular carcinoma patients, as well as cancer progression in soft tissue sarcoma .…”
Section: Introductionmentioning
confidence: 99%
“…The latter differs from the former mainly by the disruption of maternal blood vessel walls by invading fetal cells, resulting in maternal blood bathing the syncytial maternofetal interface, as observed in all hemochorial placentas, including human placenta (19). In this respect it is worth mentioning that a recent analysis of the properties of the envelope protein of the human endogenous retrovirus K (HERV-K) family of human endogenous retroviruses has provided hints that this envelope could promote an epithelial-mesenchymal phenotypic transition (EMT) as well as cellular invasion (38) and that the recently described syncytin-Mab1 seems able to modulate cell migration phenomena through interaction with its cognate receptor (16). Although preliminary assays carried out with Hyena-Env2 could not demonstrate a similar effect, a more refined experimental setup, or even better, identification of the Hyena-Env2 receptor, should now be carried out to understand in molecular terms how the captured envelope can contribute to the transition in placentation type.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, despite their obvious upregulation during prostate cancer progression, no direct oncogenic effects of Gag proteins or transcripts have been reported. Targeting HERV-K Env proteins by antibodies may interfere with the proliferation of cancer cells [15]. However, HERV-K Env expression in prostate cancer is apparently limited and has not yet been demonstrated to promote cancer growth.…”
Section: Expert Opinionmentioning
confidence: 99%
“…HERV-K Rec proteins may also bind specific RNAs and affect their translation [14], but this mechanism has not been studied in prostate cancer. In cells from other cancers, certain Env proteins are proposed to modulate signal transduction via the MAPK (mitogen-activated protein kinase) pathway and thereby cell proliferation [15]. In prostate cancer, HERV-K Env expression may be weak, presumably because of the predominant expression of env-deficient proviruses.…”
Section: Introductionmentioning
confidence: 99%